The incidence and patient outcomes of ABSSSI by iclaprim MIC values in the phase 3 REVIVE trials for treatment of acute bacterial skin and skin structure infections. Issue 6 (June 2019) - Huang, David B.; Charrier, Cedric; Le Bras, Chloé; Hawser, Stephen; Noviello, Stephanie
Abstract : N/A: The incidence and patient outcomes of Staphylococcus aureus isolates by iclaprim MIC was determined among patients from two phase 3 studies for the treatment of acute bacterial skin and skin structure infections (ABSSSI), REVIVE‐1 and ‐2. Iclaprim MIC90 values were 0.12 μg ml −1 for S. aureus (0.12 μg ml −1 against methicillin‐sensitive and 0.25 μg ml −1 against methicillin‐resistant S. aureus ). The incidence of culture confirmed S. aureus isolates among patients with ABSSSI with an iclaprim MIC > 8 μg ml −1 was 2.0 % (16/790). The clinical outcomes varied by MICs for early clinical response (63‐100 %), end of therapy response (81‐100 %) and the test of cure response (75‐100 %). For microbiological outcomes of these infections, the end of therapy response was 80‐100 % and the test of cure response was 88‐100 %.